Survival Outcomes with Hyponatremia in Paediatric Intensive Care of Tertiary Care Hospital - Akhlaq, Bilal; Nadeem, Tariq; Ikram, Farooq; Arshad, Hafsa; Kazmi, Awais; Nawaz, Syed Hassan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of mortality in patients with hyponatremia admitted in the Paediatric intensive care setting.Study Design: Cross-sectional study.Place and Duration of Study: Department of Paediatrics, Combined Military Hospital, Rawalpindi, Pakistan, from Jan to Jul 2022.Methodology: The study was based on a sample of 118 patients admitted for intensive care between the ages of 1 to 12 years with a serum sodium of less than 135 mmol/L. Patients who had artefactual hyponatremia or those who only developed the electrolyte imbalance during admission were excluded. Patients were documented for demographic data, and the degree of hyponatremia was classified according to severity, while the requirement for mechanical ventilation and inotropic support was also noted. Patients were followed up till discharge or death. Data was analyzed by SPSS 26.0.Results: We studied a population with a mean age of 5.76±3.17 years. Most of the patients, 74(57.8%) were male. Male patients tended to have a lower serum sodium level compared to females, (p=0.029). Younger patients tended to develop more severe hyponatremia, (p